Academics’ Experiences of a Post Graduate Diploma in Higher Education (PGDHE) Programme: A Case of One University in South Africa. - Machingambi, Severino (International Journal of African Higher Education, 2020)
The Post Graduate Diploma in Higher Education is widely accepted as a standard qualification that inducts and orients academics for their roles as university teachers. It equips academics with pedagogical knowledge and competencies thereby helping them to cope with the learning needs of academically under-prepared and diverse group of students. Research, conducted in South Africa and elsewhere, has shown that in order to be effective facilitators of learning, academics need to have a good blend of the knowledge of their disciplines as well as the knowledge of teaching and learning. This study sought to examine the experiences of a group of academics of studying the PGDHE. The sample for the study comprised 15 academics purposively selected from the 20 academics who had recently qualified with the PGDHE programme from one university in South Africa. The research used a qualitative methodology to collect information from the participants through an unstructured questionnaire. The major finding was that the PGDHE empowered academics significantly in their roles as university teachers and participants felt the programme should be made a pre-requisite for one’s appointment as a university teacher.